Thermodynamic analyses of the orthorhombic-to-tetragonal phase transition in Pr2−xNdxNiO4+δ under controlled oxygen partial pressures. Issue 34 (19th August 2020) - Niwa, Eiki; Sato, Tsubasa; Hashimoto, Takuya
Abstract : The standard entropy change, Δ S °, and enthalpy change, Δ H °, at the structural phase transition of Pr2− x Nd x NiO4+ δ and their impact on variation of phase transition temperature by Nd content. Abstract : The behavior of the structural orthorhombic-tetragonal phase transition of Pr2− x Nd x NiO4+ δ, a candidate material for solid oxide fuel cells and oxygen permeation membranes, was investigated by differential scanning calorimetry and thermogravimetry (TG), under controlled oxygen partial pressures, P (O2 ). The structural phase transition temperature, T P, of Pr2− x Nd x NiO4+ δ increased with increasing Nd content, x, or increasing P (O2 ). The phase transitions of all compositions involved discrete variations in the oxygen content, Δ δ, which were observed in the TG curves under various P (O2 ) values. Δ δ of Pr2− x Nd x NiO4+ δ with 0.5 ≤ x ≤ 1.5 were between those of Nd2 NiO4+ δ and Pr2 NiO4+ δ, regardless of P (O2 ), and were slightly increased with decreasing P (O2 ). It was proposed that the effect of the valence change of the Pr ion on Δ δ was decreased with increasing Nd content. The standard enthalpy change, Δ H °, and entropy change, Δ S °, of the phase transition were estimated from the Ellingham diagrams and van't Hoff plots, which were prepared from the relationship between P (O2 ) and T P using an ideal solution model. Δ S ° was decreased with increasing Nd content for the specimens with 0.0 ≤ x ≤ 1.5. The Δ H ° of Pr2− x Nd x NiO4+ δ with 0.0 ≤ x ≤ 1.5 was almost constant for all Nd contents. The increase in the phase transition temperature of Pr2− x Nd x NiO4+ δ with increasing x from 0.0 to 1.5 was successfully explained using the calculated values of Δ H ° and Δ S °.